Sucrose supplementation influences gut microbial diversity and functional shifts in Apis cerana indica - Nayak, Deeptismita; Behera, Pravasini; Singh, Satyapriya; Tripathy, Partha Sarathi; Dash, Soumya Shephalika; Dasgupta, Madhumita; Mohanty, Sansuta; Sahoo, Manas Ranjan; Satapathy, Chitta Ranjan; Sasmal, Arundhati; Sahu, Subhasmita (Frontiers in Microbiology, 2026)
Honeybee colonies are increasingly threatened by nutritional scarcity and biotic stressors, underscoring the need to understand the role of gut microbiota in mitigating these challenges. This study examined the gut microbial composition of Apis cerana indica under two dietary regimes: sucrose–fed and sucrose–unfed, to assess how nutrition influences microbial diversity and metabolic potential following metagenomics. Metagenomic sequencing of gut samples revealed 147,146 contigs, with the longest and shortest contigs measuring 615,154 kb and 200 kb, respectively. Comparative analysis indicated a higher relative abundance of Bacillus spp. in sucrose–fed bees, whereas Enterococcus was more dominant in unfed populations. Sucrose feeding significantly enhanced gut microbial diversity (Shannon index: 2.59; Simpson’s index: 0.87) compared to unfed bees (Shannon: 1.91; Simpson: 0.68). Key genera, including Gilliamella, Bacillus, and Lactobacillus, were consistently present but showed varying relative abundances. Functional annotation via KEGG pathway analysis revealed elevated activity of glycolysis and the pentose phosphate pathway in sucrose-fed bees, with exclusive detection of key metabolic enzymes, hexokinase and enolase. Additionally, elevated sucrose metabolism and proteolytic enzyme activity were noted, reflecting enhanced metabolic versatility. Our findings highlight the importance of sucrose dietary supplementation in shaping gut microbial structure and function, their diversity, and metabolic capacity, suggesting its potential as a practical nutritional intervention to sustain honeybee health during a period of floral dearth. The outcome of the study encourages exploring the long–term ecological and physiological impacts of dietary strategies on colony resilience and productivity.